The Virome of Cerebrospinal Fluid: Viruses Where We Once Thought There Were None - Ghose, Chandrabali; Ly, Melissa; Schwanemann, Leila K.; Shin, Ji Hyun; Atab, Katayoon; Barr, Jeremy J.; Little, Mark; Schooley, Robert T.; Chopyk, Jessica; Pride, David T. (Frontiers in Microbiology, 2019)
Traditionally, medicine has held that some human body sites are sterile and that the introduction of microbes to these sites results in infections. This paradigm shifted significantly with the discovery of the human microbiome and acceptance of these commensal microbes living across the body. However, the central nervous system (CNS) is still believed by many to be sterile in healthy people. Using culture-independent methods, we examined the virome of cerebrospinal fluid (CSF) from a cohort of mostly healthy human subjects. We identified a community of DNA viruses, most of which were identified as bacteriophages. Compared to other human specimen types, CSF viromes were not ecologically distinct. There was a high alpha diversity cluster that included feces, saliva, and urine, and a low alpha diversity cluster that included CSF, body fluids, plasma, and breast milk. The high diversity cluster included specimens known to have many bacteria, while other specimens traditionally assumed to be sterile formed the low diversity cluster. There was an abundance of viruses shared among CSF, breast milk, plasma, and body fluids, while each generally shared less with urine, feces, and saliva. These shared viruses ranged across different virus families, indicating that similarities between these viromes represent more than just a single shared virus family. By identifying a virome in the CSF of mostly healthy individuals, it is now less likely that any human body site is devoid of microbes, which further highlights the need to decipher the role that viral communities may play in human health.